Differential expression of CRAC channel in alloxan induced Diabetic BALB/c mice. (2nd January 2020) - Ramakrishnan, Anantha Maharasi; Kumar, Pavitra; Chatterjee, Suvro; Sankaranarayanan, Kavitha
Abstract: Objectives: CRAC (Calcium Release Activated Calcium) channel is one of the most important channels regulating calcium influx and has been involved in many autoimmune diseases. The contribution of CRAC channel in the pathogenesis of Type 1 Diabetes (T1D) has not been described much. Thus, we aimed to study the expression of CRAC channel and inflammatory cytokines like IL-1β (Interleukin -1β) and TNF-α (Tumor Necrosis Factor-α) in the spleen-derived cytotoxic T cells, Bone marrow monocytes (BMM) and macrophages differentiated from BMM in the alloxan induced T1D mice. Materials and methods: BALB/c mice treated with alloxan and vehicle control for 12 and 24 h. Spleen derived T cells; Bone marrow derived monocytes were isolated from the control and diabetic BALB/c mice as well as macrophages differentiated from the control and diabetic BMM. Results: We observed increased expression of CRAC channel components like STIM1 (Stromal Interaction Molecule), ORAI1 and ORAI2 and inflammatory cytokines like IL-1β and TNF-α in the spleen derived cytotoxic T cells and Macrophages differentiated from BMM as well as the downregulated expression of the same and CRAC channel in BMM of 12 and 24 h alloxan induced BALB/c mice. Conclusions: This study suggests that differential expression of CRAC channel correlated with the expression of inflammatory cytokines, thus CRAC channel might be responsible for the increased production of inflammatory cytokines in the alloxan induced T1D mice.